The Paradigm of Knowledge in Search of Alternative Science - Ridha Ahida (Refleksi: Jurnal Kajian Agama dan Filsafat, 2007)
Many things need to be considered when developing knowledge in human life. On one hand, knowledge plays a crucial role in every aspect of human life; the exploration of knowledge has provided a series of conveniences in human activities, and technological advancements resulting from scientific knowledge have accelerated human mobility. However, on the other hand, the development of scientific knowledge and its role has seemingly undermined human existence. Scientific knowledge is no longer just explored but exploited to the fullest. As a result, scientific knowledge has threatened and even destroyed human existence. This article discusses the need for a paradigm that will guide the development of scientific knowledge to remain constructive in human life.